Bacteriological Quality of Panipuri in Historical Gwalior City (MP), India - Mishra, Raghvendra Kumar (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The food safety is becoming a serious threat to public health, particularly in developing countries. In common street foods, vendors are using normal water without any treatment. The consumption of street foods is very popular in India and all over the world. Materials and Methods: In food samples, the microbiological analysis was done to determine the bacteria, including pathogenic bacteria. Results: Different bacterial cultures were isolated from 20 samples of panipuri collected from different locations of Gwalior, Madhya Pradesh, India. The dominant contaminant bacteria reported in the study were from Enterobacteriaceae family including Proteus vulgaris and Klebsiella pneumoniae. The antibacterial efficacy of silver nanoparticles (AgNPs) was tested against isolated bacteria. Antibacterial activity showed that AgNPs synthesized had a good antibacterial activity to kill foodborne pathogens. Although it is a preliminary data, it will increase our understanding of the presence of bacteria in street food as well as the use of AgNPs as antibacterial agents. Conclusion: The risks associated with street foods may be controlled by clean water and maintaining proper hygienic conditions.